Dzienniki Marii Dąbrowskiej: przygody człowieka etycznego - Rodak, Paweł (Kultura i Społeczeństwo, 2008)
In analysing the complete diaries, the author points out that they are a speciﬁc form of personal document in which we encounter a doubly personalised approach to the world (through the author of the diaries and those who appear in the diary because they feature in her life). In the diary Dąbrowska is completely turned towards the world – primarily towards the other person (an exocentric, not egocentric, diary). It is from the point of view that the author describes four basic lines of tension in the diary – the private–public, the personal–social and historic, the internal–external, the conscious–subconscious, as well as its important function (keeping a balance of a situation of almost permanent crisis which is a part of the relationship between “me” and the world). Later, the author points to the most important components of Dąbrowska’s consciousness (the interrelated experiences of danger and the secrets of existence, the reality of the other person and its values and the undiminished ties which link people constituting a metaphysical and ethical component of their condition) and their sources (Abramowski, Conrad). The description of Dąbrowska identiﬁes her embracing the “ethos of the democratic Polish intelligentsia” as well as her particular place within it. At the end the author emphasises that Dąbrowska’s private version as presented in the manuscripts of the diary is more authentic and real than the published version and that it demands the earliest possible publication of the whole diary in a philological edition (without footnotes), followed by academic work on it using the full critical apparatus.